Poeticizing Ecology/Ecologizing Poetry: Reading Elizabeth Bishop’s “Poem” Ecologically - Spicer, Kevin Andrew; McDermott, Beth (The Trumpeter, 2017)
In “Poeticizing Ecology/Ecologizing Poetry: Reading Elizabeth Bishop’s ‘Poem’ Ecologically,” we argue that ecological poetry is a kind of ecopoetry that undergirds “nature poetry” and environmental/activist poetry.  Ecological poetry is also best put into conversation with deconstruction.  This argument, informed by Timothy Morton’s claim that “deconstruction and ecology should talk to one another,” entails challenging previous arguments about what counts as ecopoetry but also the status of the lyric in general.  We synthesize James Longenbach’s position in The Resistance of Poetry with Nick Selby’s argument in “Ecopoetries in America” to examine the relationship between close reading and reading ecologically.  Rather than an ethical stance perceived in the content of the poem, to read ecologically requires attention to form and linguistic indeterminacy, not only because deconstruction and ecology are alike, but also because poetry is comprised of language, the usage of which “revels in duplicity and disjunction.” Deconstruction is the best approach to divergent perspectives on nature, or the way a poem offers, in Nick Selby’s view, not a clear purchase or single overarching view, but “a struggle to get nature right.”  We contend that to give space to alterity, to allow the otherness not only of nature but also of language itself in its capacity for referentiality is to expand the “marked” space of ecology (in the terms set forth by G. Spencer Brown’s Laws of Form).  We support this claim with a reading of Bishop’s “Poem,” which we acknowledge as an atypical choice for what constitutes ecological poetry.  A borderline ekphrastic poem, “Poem” allows us to talk not only about the space inherent in nature and language but between text and image, or poem and painting.  What we find in our reading of Bishop’s “Poem” is a contingency between the poem and the painting, rather than a classical attempt of one to overpower the other, to speak for the other as the more authoritative sign.  We find the uncanny or strange quality of Bishop’s ekphrastic approach to an amateurish painting that she calls “sketch” a way to further substantiate Morton’s claim about the relevance of deconstruction to ecology.  Through our reading of the poem we argue that no entity completely coincides with itself because ecological thinking has helped us to see how every entity is shot-through with traces of the other; we ourselves are made up of other lifeforms; life is made up of nonlife.  To think ecologically is to think the other within the self (especially including all the nonhuman others), within any entity whatsoever.